the sum you have stated is 2-3x2-4
bomdas. multiply before subtraction. therefore 2(-3x2)-4, becomes 2-6-4, which is -8
Using the symbol "^" for power. (-3)^1 * (-3)^(1/3) = (-3)^(4/3).
4 and 2/3
2-3/5-4 = 2-0.6-4 = -2.6
When you simplify a fraction this means you are making the fraction you have into a smaller fraction that is easier to use when you solve a problem Example: 3/6 + 1/4 you would SIMPLIFY 3/6 into 1/2 and add 1/2 to 1/4 to get an answer of 3/4
you cannot simplify 3/4 because 3 and 4 do not divide by the same thing.To simplify you need to be able to divide the numerator and the denominator by the same number, for example:2/4 could be simplified to 1/2 because 2 and 4 both divide by 2.You can't simplify 3/4 any further. The denominator is already as small as it can be.
2
-2
Step 1: Ignore the signs, just simplify the fraction.Step 2: Count the number of negative (minus) signs. If there is one, then the answer is negative, otherwise it is positive.Step 2 can also be stated thus:-/- or +/+ = plus-/+ or +/- = minusSo, -12/412/4 = 3 and there is only 1 negative sign so the answer is negative.Answer: -3.Hope that explains it.
-24 cannot be simplified.
Using the symbol "^" for power. (-3)^1 * (-3)^(1/3) = (-3)^(4/3).
-2
4 and 2/3
2-3/5-4 = 2-0.6-4 = -2.6
When you simplify a fraction this means you are making the fraction you have into a smaller fraction that is easier to use when you solve a problem Example: 3/6 + 1/4 you would SIMPLIFY 3/6 into 1/2 and add 1/2 to 1/4 to get an answer of 3/4
4
3*4*2 = 12*2 = 24
6